Some thoughts concerning power sums - Nyul, Gábor (Teaching Mathematics and Computer Science, 2015)
In this note we present an elementary way to derive directly closed-form expressions for power sums. Applying this method, we deduce some general results on power sums with arbitrary exponents. Finally, we give an outlook on higher mathematical connections between power sums, Stirling and Bernoulli numbers.